Quadrupolar interaction induced frequency shift of 131Xe nuclear spins on the surface of silicon. (1st September 2022) - Chen, Yao; Yu, Mingzhi; Ma, Yintao; Wang, Yanbin; Guo, Ju; Lin, Qijing; Zhang, Ning; Jiang, Zhuangde; Zhao, Libo
Abstract: The combination of micro-machined technology with atomic spin gyroscope (ASG) devices can be used to fabricate a chip-scale atomic spin gyroscope (CASG). The core of the gyroscope is a micromachined vapour cell, which contains alkali metal and isotope-enriched noble gases, such as 129 Xe and 131 Xe . The quadrupolar frequency shift of 131 Xe is a key parameter that can affect the drift of the ASG and is related to the material of the cell in which they are contained. In micromachining technology, the utilised material is silicon. In this study, we investigated the electric quadrupolar frequency shift of 131 Xe atoms with the silicon wall of a micro-machined vapour cell. A cylindrical micromachined vapour cell was utilised in the experiment, and a large part of the inner cell surface comprised silicon material. We studied the temperature dependence of the 129 Xe spin relaxation and 131 Xe frequency shifts to evaluate the interaction of the nuclear spin with the container wall and alkali metal atoms. The results show that the average twisted angle of the 131 Xe nuclear spins as they collided with the silicon wall was measured as 29 × 10 − 6 rad. The desorption energy required for the 131 Xe nuclear spin to escape from the silicon surface was E s i = 0.009   eV . This study could help improve the bias stability of the CASG, which is a key parameter for the gyroscope, and may help to develop a method to study the surface properties of various materials.